Naturalisation and investments in children's human capital: Evidence from a natural experiment - Friederike von Haaren-Giebel (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2016)
This paper assesses educational attainment of immigrant children, in particular evaluating whether naturalised parents invest more in their children's human capital than non-naturalised parents. Findings of the literature indicate that citizenship is associated with lower return migration probability. Since the returns to investments in (country-specific) human capital increase with the duration of residence, naturalised parents may have more incentives to invest in the educational success of their children. I exploit a natural experiment that took place in Germany in the year 2000 that reduced the required years of residence for naturalisation from 15 to 8 and therefore exogenously increased naturalisation. Multivariate estimations (based on the German Socio-Economic Panel) show a positive and significant correlation between parents' citizenship status and their children's educational attainment. Results of difference-in-differences and instrumental variable models are also positive but not significant.
Keywords: J15; J24; I24; 330; citizenship; integration; education; SOEP